PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP NILAI PERUSAHAAN - ERNI KURNIASARI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This research aims to determine the influence of current ratio, debt to equity ratio, total asset turnover on firm value partially and simultaneously. The population in this research are food and beverages companies listed on the Indonesian Stock Exchange in the period 2015-2019. The sample selection used purposive sampling method. The sample in this research are 10 food and beverages companies listed on the Indonesian Stock Exchange in the period 2015-2019. Based on the results of this research, the researcher concludes that partially the debt to equity ratio and total asset turnover have a significant influence on firm value, while the current ratio has no significant influence on firm value. Simultaneously, the current ratio, debt to equity ratio and total asset turnover have a significant influence on firm value. The coefficient of determination is 0,541, showed that the current ratio, debt to equity ratio and total asset turnover have 54,1% to the firm value, while 45,9% are determined by another variables.